Synthetic Peptides Derived From Lycosa Erythrognatha Venom: Interaction With Phospholipid Membranes and Activity Against Resistant Bacteria - Reis, Pablo V. M.; Lima, Vinícius M.; Souza, Kelton R.; Cardoso, Gabriele A.; Melo-Braga, Marcella N.; Santos, Daniel M.; Verly, Rodrigo M.; Pimenta, Adriano M. C.; Santos, Vera Lúcia dos; de Lima, Maria Elena (Frontiers in Molecular Biosciences, 2021)
Super-resistant bacteria are a public health problem, increasing the need of new drugs and strategies to combat them. Our group has previously identified LyeTxI, an antimicrobial peptide isolated from Lycosa erythrognatha spider venom. From LyeTxI, we have synthesized and characterized a derived peptide named LyeTxI-b, which has shown great in vitro and in vivo activity. In this work, we elucidate the interaction of LyeTxI-b with artificial membranes as well as its effects on resistant strains of bacteria, in planktonic conditions and in biofilms. Isothermal titration calorimetry revealed that LyeTxI-b interacts more rapidly and with higher intensity with artificial vesicles, showing higher affinity to anionic vesicles, when compared to synthetic LyeTxI. In calcein experiments, LyeTxI-b caused greater levels of vesicle cleavage. Both peptides showed antibacterial activity at concentrations of μmol.L-1 against 12 different clinically isolated strains, in planktonic conditions, in a concentration-dependent manner. Furthermore, both peptides elicited a dose-dependent production of reactive oxygen species in methicillin-resistant Staphylococcus aureus. In S. aureus biofilm assay, LyeTxI-b was more potent. However, none of these peptides reduced Escherichia coli biofilm. Our results show LyeTxI-b as a promising drug against clinically resistant strains, being a template for developing new antibiotics.